Cyanocypus gen. nov., a new rove beetle genus of the “Staphylinus-complex” (Coleoptera: Staphylinidae) with one new species from China - He, Liang; Zhou, Hong-Zhang (Zootaxa, 2020)
This paper reports one new genus, Cyanocypus gen. nov. and one new species, Cyanocypus leukos sp. nov. from Yunnan, China. A comparison between the new genus and other related genera is provided and the diagnostic characters are illustrated.